Combination of Metformin, Sodium Oxamate and Doxorubicin Induces Apoptosis and Autophagy in Colorectal Cancer Cells via Downregulation HIF-1α - Coronel-Hernández, Jossimar; Salgado-García, Rebeca; Cantú-De León, David; Jacobo-Herrera, Nadia; Millan-Catalan, Oliver; Delgado-Waldo, Izamary; Campos-Parra, Alma D.; Rodríguez-Morales, Miguel; Delgado-Buenrostro, Norma L.; Pérez-Plasencia, Carlos (Frontiers in Oncology, 2021)
Colorectal cancer is the third leading cause of cancer-related death worldwide in both sexes; current therapies includes surgery, chemotherapy and targeted therapy; however, prolonged exposure to chemical agents induce toxicity in patients and drug resistance. So, we implemented a therapeutic strategy based on the combination of doxorubicin, metformin and sodium oxamate called triple therapy (Tt). We found that Tt significantly reduced proliferation by inhibit mTOR/AKT pathway and promoted apoptosis and autophagy in CRC derived cells compared with doxorubicin. Several autophagy genes were assessed by western blot and ULK1, ATG4 and LC3 II were found overexpressed by Tt. Interestingly, ULK1 was the only one autophagy related protein gradually overexpressed during Tt administration, thus we presumed that there was a post-transcriptional mechanism mediating by microRNAs that regulate UKL1 expression during autophagy activation. By means of bioinformatic approaches, we found that ULK1 could be targeted by mir-26a, which is overexpressed in advanced stages of CRC. In vitro experiments revealed that overexpression of mir-26a decreased significantly ULK1 mRNA and protein expression, contrariwise, the Tt recovered ULK1 expression by mir-26a decrease. Due to triple therapy repressed mir-26a expression, we hypothesized this drug combination could be involve in mir-26a transcription regulation. Thus, we analyzed the mir-26a promoter sequence and we found two HIF-1a transcription factor recognition sites. We developed two different HIF-1a stabilization models and they showed mir-26a overexpression and ULK1 reduction in hypoxic conditions. Immunoprecipitation experiments were performed and HIF-1a enrichment was observed in mir-26a promoter. Surprisingly, triple therapy diminished HIF-1a detection and restore ULK1 mRNA expression. These results show an important regulation mechanism controlled by the signaling that activates HIF-1a and that in turn regulates mir-26a transcription.